Analysis of health behaviours among athletes and football players - Karpińska, Anna (Journal of Education, Health and Sport, 2019)
Introduction: Sport is considered one of the oldest educational areas and forms of entertainment for mankind since antiquity. Over time, many new sports have been distinguished, among which,the most popular in Poland are: athletics and football. Athlete's image suggests that they take care for their health, and that their health behaviours should be the most intense.Aim of the study: The aim of the study was to assess the severity of health behaviours among athletes and football players, as well as to compare and analyze their results.Material and methods: The study included 100 sportsmen: 50 athletes and 50 footballers in the age range of 16-22 years. To assess health behaviors, the Inventory of Health Behaviors according to Z. Juczyński has been used.Results: Analysis of the results showed that the football players are sportsmen who care more about their health. The result of their average health behaviour index was higher than in the case of athletes. The vast majority of athletes were assigned to the group with the average level of health behaviours, while the most football players were placed in the group showing high-quality health behaviours. However, taking into account the Sten average , all of them can be classified as mid-level results. In both disciplines, the lowest results were achieved in the category of "correct eating habits", the highest in the "positive psychological attitude" category.Conclusions: The study showed that sportsmen against the rest of the society do not show a high level of health behaviours. However, among them football players are more health-oriented than athletes.